3D MXene anchored carbon nanotube as bifunctional and durable oxygen catalysts for Zn–air batteries. (15th November 2021) - Zhang, Chao; Dong, Huifeng; Chen, Binling; Jin, Tianxu; Nie, Jun; Ma, Guiping
Abstract: The development of bifunctional activity and long durability of ORR/OER catalyst is vital for realizing the practical application of Zn–air batteries (ZAB). Herein, 3D-structured bifunctional catalysts, CoFe nanoalloy decorated carbon nanotubes (CNT) anchoring with 2D MXene (Fe/Co-CNT@MXene-T), were prepared and fabricated as the cathode for both aqueous and flexible ZAB. Taking advantages of active sites of CoFe nanoparticles, robust sheath and fast charge transfer provided by CNT and MXene, our optimal catalyst Fe/Co-CNT@MXene-8 exhibited remarkable electroactivities of ORR and OER comparable with the benchmark Platinum carbon (Pt/C) and Ruthenium dioxide (RuO2 ), respectively. The as-assembled aqueous ZAB with Fe/Co-CNT@MXene-8 as cathode exhibited a high specific capacity of 759 mA h g −1  at a current density of 10 mA cm −2, and a stable voltage platform in the quick discharge–charge test under a 375h long-lasting operation, superior to those assembled with benchmark commercial catalyst and other reported catalysts. Furthermore, the as-assembled flexible ZAB with Fe/Co-CNT@MXene-8 as cathode also presented excellent durability cycling and showed promising perspectives as future power sources for wearable application. Such high performance was also verified by X-ray absorption near-edge structure (XANES) and supported by density functional theory (DFT) calculation. This work provides a novel view to design highly effective and long-lasting rechargeable ZABs. Graphical abstract: FeCo alloy nanoparticles encapsulated N-doped carbon nanotubes (CNT) have been successfully anchored on the surface of N-doped MXene. Image 1 Highlights: FeCo alloy nanoparticles encapsulated N-doped carbon nanotubes (CNT) have been anchored on the surface of N-doped Mxene. The 3D conductive network exhibited excellent ORR performance. The Zn-air battery showed 375h discharge and cycle performance.